Age Is Important for the Early-Stage Detection of Breast Cancer on Both Transcriptomic and Methylomic Biomarkers - Feng, Xin; Li, Jialiang; Li, Han; Chen, Hang; Li, Fei; Liu, Quewang; You, Zhu-Hong; Zhou, Fengfeng (Frontiers in Genetics, 2019)
Patients at different ages had different rates of cell development and metabolisms. So age should be an essential part of how a disease diagnosis model was trained and optimized. Unfortunately, most of the existing studies did not take age into account. This study demonstrated that disease diagnosis models could be improved by merely applying individual models for patients of different age groups. Both transcriptomes and methylomes of the TCGA breast cancer dataset (TCGA-BRCA) were utilized for the analysis procedure of feature selection and classification. Our experimental data strongly suggested that disease diagnosis modeling should integrate the patient age into the whole experimental design.